Granular Subbase Improvement with Recycled Concrete Aggregates in Tropical Areas - Vega A., Daniela L.; Salcedo Fontalvo, Jose Eduardo; Jimenez Triana, Richard; Palacios del Barre, Dulce Maria; Fresneda Saldarriaga, Cesar (IIUM Engineering Journal, 2022)
Use of Recycled Concrete Aggregate (RCA) for Granular Subbase (GSB) in the tropical area is evaluated in this work. Among the materials widely studied as replacements in granular and surface layers is RCA. Its mechanical behavior in granular layers has mainly been evaluated with tests such as California Bearing Ratio (CBR). However, abrasion is also a determining property in the strength of these materials. In this study, the performance of Natural Aggregates (NA) with replacement of RCA was evaluated for use as GSB in a tropical area. Even though several laboratory tests were performed, the focus of the article lies on the performance in the Los Angeles (LA) abrasion test. Two replacement percentages of coarse RCA were considered: 10 and 15 % by weight of aggregates. The RCA and NA were characterized according to different laboratory tests: Granulometry, Absorption, Atterberg Limits test, Plasticity, Specific Gravity, and LA abrasion. In turn, all results were compared with Colombian specifications for a typical GSB in the area. In addition, a simple Life Cycle Assessment (LCA) was included to evaluate the environmental impacts of the base and alternative scenarios. The results show that GSB with 10% RCA present a higher abrasion resistance than the GSB with 15% RCA. Even better results are obtained with 10% RCA than with natural GSB. Specifically, average LA abrasion test losses of 30.86, 29.80 and 32.07% were obtained for NA, 10% RCA and 15% RCA, respectively. The LCA results show an increase of 50% and 75% in energy consumption by comparing the base scenario with 10 and 15% RCA replacement, respectively. This leads to an increase of 40 and 80% in carbon monoxide (CO) emissions for 10 and 15% RCA replacement respectively, and 100% in carbon dioxide (CO2) emissions for both alternative scenarios. ABSTRAK: Penggunaan Agregat Konkrit Kitar Semula (RCA) bagi Subtapak Butiran (GSB) bagi kawasan tropika telah dikaji dalam kajian ini. Antara bahan yang banyak dikaji sebagai bahan ganti dalam butiran dan lapisan permukaan adalah RCA. Ciri-ciri mekanikal dalam lapisan butiran telah diuji, terutamanya dengan ujian seperti Nisbah Bearing California (CBR). Walau bagaimanapun, pelelasan juga merupakan ciri penting dalam menentukan ketahanan material. Kajian ini merupakan prestasi Agregasi Semulajadi (NA) dengan ganti RCA yang diuji bagi penggunaan GSB di kawasan tropika. Walaupun pelbagai ujian makmal telah dijalankan, fokus artikel ini terletak pada prestasi ujian pelelasan Los Angeles (LA). Dua gantian bagi peratus RCA kasar telah diambil kira: iaitu pada agregat berat 10% dan 15%. Ciri-ciri RCA dan NA dikategori berdasarkan pelbagai ujian lab yang pelbagai: Granulometri, Penyerapan, ujian Had Atterberg, Keplastikan, Graviti Tertentu dan Pelelasan LA. Kemudian, kesemua dapatan kajian dibandingkan dengan ciri-ciri Kolombia bagi ciri tipikal GSB di kawasan itu. Tambahan, Pentaksiran Kitar Hidup (LCA) yang ringkas dimasukkan bagi menilai impak terhadap alam terhadap penggunaanya pada pangkal bijirin dan pada senario alternatif. Dapatan kajian menunjukkan GSB yang menggunakan RCA 10% mempunyai rintangan lelasan tertinggi berbanding GSB dengan RCA 15%. Tambahan, dapatan kajian yang lebih baik didapati daripada RCA 10% berbanding GSB semula jadi. Terutama pada purata ujian lelasan LA telah mengalami penyusutan sebanyak 30.86, 29.80 dan 32.07% bagi NA, RCA 10% dan RCA 15%, masing-masing. Dapatan LCA menunjukkan peningkatan sebanyak 50% dan 75% pada penggunaan tenaga dengan perbandingan senario Subtapak Butiran dengan gantian RCA 10% dan 15%, masing-masing. Ini membawa kepada peningkatan sebanyak 40% dan 80% emisi karbon monoksida (CO) bagi gantian RCA 10% dan 15% masing-masing, dan emisi karbon dioksida (CO2) 100% bagi kedua-dua senario alternatif.